Property rights and participatory forest management: an overview - Moeliono, M. (ATSE Crawford Fund, 2002)
This paper is an overview of participatory forest management in relation with property rights issue. It highlights the difficulty in defining property rights. Although the issues presented are applicable throughout tropical Asia, albeit less so in the Pacific, this paper is based primarily on the author's experience in Indonesia, and almost all of examples are from indonesia. This paper discuss the diversity and changing nature of property rights and continues with a discussion on the issue of communities demanding the rights and possible responses of the government. At the end it presents a short review on participation of local communities in forest management.